Research on cutting mechanism of ZnGeP2 crystal under surface brittle-plastic transition by heating assistance. (1st March 2021) - Cao, Zhonghao; Liu, Youhai; Yang, Hong; Sun, Shouli; Zhang, Min; Dai, Xiaojing
Abstract: Improving the surface quality of the ZnGeP2 crystal is an important way to expand its application range. Given the high difficulty of processing the ZnGeP2 crystal, the research proposed a method of increasing the processing temperature of the material to expand the range of the plastic region, then improving the surface quality, the feasibility of the method was verified by heating assisted nanoindentation experiment and molecular dynamics simulation. The use of diamond tools to scribe the surface revealed the microscopic morphology changes of the ZnGeP2 crystal under high temperatures. Finally, with the assistance of heating, the surface of ZnGeP2 crystal was processed comprehensively by ultra-precision diamond fly-cutting machine, the experimental results showed that as the processing temperature increased, the surface quality of the ZnGeP2 crystal gradually improved, and the surface roughness Sa could reach to 9.426 nm. The effectiveness of improving the surface quality through heating assisted cutting was verified, which had guiding significance for the processing of other hard and brittle materials. Highlights: The theory of improving the surface quality of ZnGeP2 by heating assisted processing was put forward. The feasibility of the theory was verified by molecular dynamics simulation and heating assisted nano-indentation. The influence of heating assistance on the surface quality of ZnGeP2 was analyzed. The surface roughness of ZnGeP2 obtained by heating assistance was higher, up to 9.426 nm.